2019
DOI: 10.7759/cureus.4469
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Femoral Neck Anteversion in Adults: A Comparison Between Clinical Method, Radiography, and Computed Tomography at a Tertiary-care Center in Eastern India

Abstract: Introduction Femoral anteversion is the anterior inclination of the femoral neck and head in relation to the shaft of the femur. Femoral anteversion provides torsional stability of the hip - an important clinical factor for conditions such as trauma, arthroplasty, developmental dysplasia of the hip, and Legg-Calve Perthes disease. Precise measurement is important to avoid instability in pathological conditions of the hip. Computed tomography (CT) measures the angle more accurately as compared to pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…As for measures of acetabulum abduction, acetabulum anteversion, and femoral anteversion, we did not find statistical differences between males and females. Our findings are in agreement with previous studies (35, 43,44) but in contrast to others that have reported significant sex differences in acetabulum abduction (45)(46)(47), acetabulum anteversion (40,(44)(45)(46)(47), and femoral anteversion (38,40). Inconsistent findings in literature could be a result of different methodologies used to obtain morphological measurements (2D vs 3D).…”
Section: Discussionsupporting
confidence: 92%
“…As for measures of acetabulum abduction, acetabulum anteversion, and femoral anteversion, we did not find statistical differences between males and females. Our findings are in agreement with previous studies (35, 43,44) but in contrast to others that have reported significant sex differences in acetabulum abduction (45)(46)(47), acetabulum anteversion (40,(44)(45)(46)(47), and femoral anteversion (38,40). Inconsistent findings in literature could be a result of different methodologies used to obtain morphological measurements (2D vs 3D).…”
Section: Discussionsupporting
confidence: 92%
“…One of the evaluators using a goniometer established the zero grade angle; the other evaluator palpating the large trochanter performed the internal rotation of the hip until its most lateral point was reached. The goniometer evaluator measures the degrees of rotation in relation to the initial point, the normal value being between 8º and 15º and, above that, the anteversion of the femoral neck 5,6 . Both examiners presented similar results of the daily measurement established in tests before the actual collection.…”
Section: Methodsmentioning
confidence: 99%
“…A clinical measurement is through Craig's test, also called trochanteric prominence test, which has a level of accuracy close to the tomographic evaluation of the angulation and has the advantages of low cost and easy performance. Its clinical practice is justified because it generates values equivalent to the three-dimensional tests 5,6 . Recent studies validated the femoral anteversion angulation using Craig's test in comparison to measures obtained in computed tomography (CT) in children, however, there are not many records of the test in a young adult population 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Initially, FNA measurement was usually done by biplane X-ray method. However, biplane X-ray method provides spatial superposition information, and especially, the patient position is uncertain while radiographing, so many scholars believe that this method is inaccurate [ 11 , 12 ]. In recent years, the researchers gradually shifted their focus on how to measure FNA on CT images.…”
Section: Introductionmentioning
confidence: 99%